The Outbreaks of Acute Encephalitis Syndrome in Uttar Pradesh, India (1978–2020) and Its Effective Management: A Remarkable Public Health Success Story - Srivastava, Neha; Deval, Hirawati; Mittal, Mahima; Kant, Rajni; Bondre, Vijay P. (Frontiers in Public Health, 2022)
Introduction Acute encephalitis syndrome (AES) is a major public health enigma in India and the world. Uttar Pradesh (UP) is witnessing recurrent and extensive seasonal AES outbreaks since 1978. Government of India and UP state government have devised various mitigation measures to reduce AES burden and AES associated mortality, morbidity and disability in Uttar Pradesh. The aim of this study was to describe the public health measures taken in order to control seasonal outbreaks of AES in UP between 1978 and 2020. Methods We used literature review as a method of analysis, including the Indian government policy documents. This review utilized search engines such as PubMed, Google Scholar, Research Gate, Cochrane, Medline to retrieve articles and information using strategic keywords related to Acute Encephalitis Syndrome. Data was also collected from progress reports of government schemes and websites of Indian Council of Medical Research (ICMR), National Vector Borne Disease Control Programme (NVBDCP) and Integrated Disease Surveillance Programmes (IDSP). Results The incidence of AES cases in UP have declined from 18.2 per million population during 2005-2009 to 15 per million population during 2015-2019 [CI 12.6–20.6, P-value < 0.001] and case fatality rate (CFR) reduced from 33% during 1980-1984 to 12.6% during 2015-2019 [CI 17.4–30.98, P-value < 0.001]. AES incidence was 9 (2019) and 7 (2020) cases per million populations respectively and CFR was 5.8% (2019) and 5% (2020). This decline was likely due to active surveillance programs identifying aetiological agents and risk factors of AES cases. The identified etiologies of AES include Japanese encephalitis virus (5–20%), Enterovirus (0.1–33%), Orientia tsutsugamushi (45–60%) and other viral (0.2–4.2%), bacterial (0–5%) and Rickettsial (0.5–2%) causes. The aggressive immunization programs against Japanese encephalitis with vaccination coverage of 72.3% in UP helped in declining of JE cases in the region. The presumptive treatment of febrile cases with empirical Doxycycline and Azithromycin (EDA) caused decline in Scrub Typhus-AES cases. Decrease in incidence of vector borne diseases (Malaria, Dengue, Japanese Encephalitis and Kala Azar) i.e., 39.6/100,000 population in 2010 to 18/100,000 population in 2017 is highlighting the impact of vector control interventions. Strengthening healthcare infrastructure in BRD medical college and establishment of Encephalitis Treatment Centre (ETC) at peripheral health centres and emergency ambulance services (Dial 108) reduced the referral time and helped in early treatment and management of AES cases. The AES admissions increased at ETC centres to 60% and overall case fatality rate of AES declined to 3%. Under clean India mission and Jal Jeevan mission, proportion of population with clean drinking water increased from 74.3% in 1992 to 98.7% in 2020. The proportion of household having toilet facilities increased from 22.9% in 1992 to 67.4% in 2020. Provisions for better nutritional status under state and national nutrition mission helped in reducing the burden of stunting (52%) and wasting (53.4%) among under five children in 1992 to 38.8% (stunting) and 36.8% (wasting) in year 2018. These factors have all likely contributed to steady AES decline observed in UP. Conclusion There is a recent steady decline in AES incidence and CFR since implementation of intensive AES surveillance system and JE immunization campaigns which is highlighting the success of interventions made by central and state government to control seasonal AES outbreaks in UP. Currently, AES incidence is 9 cases per million population (in year 2019) and mortality is 5.8%.